RUMAH SAKIT JIWA DENGAN KONSEP HEALING ENVIRONMENT DI KOTA SEMARANG - Della Ratamanjari; Hadi Setyawan; Leny Pramesti (ARSITEKTURA, 2015)
Designing Psychiatric Hospital in Semarang City is motivated by the imbalance between the capacity of the number of psychiatric hospital beds compared to the number of cases of mental illness visits in one year in the city, the lack of adequate mental hospital that already exists, and the problems that arise from the lack of effectiveness of the healing process in conventional mental hospital. The purpose of this issue is to obtain a mental hospital design that can address the needs of all people with mental disorders all around ex-residentie of Semarang and support the healing process of patients with mental disorders. The design problem is: how to apply architectural elements that can provide a positive influence on the psychological aspects of building users. The method used is based on the concept of healing environments. The result obtained is a psychiatric hospital that makes architectural elements as a part of the healing process. Keywords: Psychiatric hospital, healing environment.